Evaluation of Antioxidant properties, knowledge, attitude and practice (KAP) on selected dietary supplements (barley grass, wheatgrass and chlorella vulgaris powders) - Azlan, Azrina; Wan, Gan Ying; Hao, Yuan Yoh; Sultana, Sharmin (Universiti Putra Malaysia, 2023)
Introduction: Three selected dietary supplements (DS), barley grass (BG), wheatgrass (WG), and Chlorella vulgaris (CV), are commercially available. However, more information is needed about the antioxidant properties of the three DS and their potential health benefits on adults’ health and well-being. Thus, this study aimed to determine the antioxidant properties and adults’ knowledge, attitudes and practices (KAP) of the three selected DS. Methods: In phase 1, an experimental study was conducted on antioxidant analysis, total phenolic content (TPC) and DPPH radical scavenging activity for the three DS. For phase 2, a cross-sectional survey (n=338) was conducted for the three DS through an online platform where convenience sampling was performed. Results: In phase 1, BG (2.83±0.50mg GAE/g DW) had the highest TPC, followed by WG (2.02±0.20mg GAE/g DW) and CV (1.74±0.65mg GAE/g DW); DPPH radical scavenging activity, BG (198.23±0.15µg/mL) and WG (177.25±0.17µg/mL) had lower IC50 compared to CV (1185.84±0.28µg/mL). Significant differences (p<0.05) were found between IC50 of the three DS and standards, butylated hydroxytoluene (24.51±0.37µg/mL) and quercetin (26.04±0.55µg/mL). While in phase 2, poor knowledge (51.5%), moderate attitude (39.6%), and poor practice (43.2%) levels were observed in most of the participants. Moreover, working adults reported higher scores in knowledge (3.70±1.51) compared to students (3.33±1.63, p=0.037). Males had higher scores (29.27±2.42) in attitude compared to females (28.49±2.68, p=0.030). Besides, participants who were single and completed tertiary education with 4-6 years of working experience showed better practice scores. The overall knowledge (r=0.134, p=0.013) and attitude (r=0.273, p<0.001) scores correlated significantly with practice scores. Conclusion: Participants’ poor knowledge, moderate attitude, and inadequate practice in phase 2 caution against over-reliance on supplements, emphasizing the importance of an active lifestyle and balanced diet for optimal health and longevity.